Tinjauan Yuridis Jual Beli Tanah Warisan Tanpa Sepengetahuan Ahli Waris Yang Lain dalam Kitab Undang-Undang Hukum Perdata (Studi Kasus Putusan Nomor 10/Pdt.G/2019/PN Lbt) - Maria Oktafiani Wona Ledun; Agustinus Hedewata; Husni Kusuma Dinata (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research discusses the juridical review of the sale and purchase of inherited land without the knowledge of other heirs in the civil law code. This research method uses normative legal research methods, namely library research methods. The results of this study indicate that the transfer of land rights through sale and purchase or inheritance and other legal events are in accordance with applicable regulations, namely the Basic Agrarian Law and Government Regulation No. 24 of 1997 to create legal certainty and justice for severe parties, all legal acts or legal events need to be contained in an authentic deed made before a Notary / PPAT and registered with the land office so that the legal act is valid and has legal force in order to avoid legal problems and disputes, as well as an analysis of the basis for the judge's consideration in Decision Number 10/PDT. G/2019/PN LBT the plaintiff's lawsuit was declared unacceptable or rejected because the main petitum of the lawsuit was rejected, the next petitum was also rejected because it was assessor / following the granting of the main petitum of the lawsuit regarding the unlawful act of the defendants was declared unacceptable.